Phylogenetic relationship analysis of leafhopper subfamily Iassinae (Hemiptera: Cicadellidae) based on low-coverage whole-genome data - Xiaozhen Lu; Jikai Lu; Yunfei Wu; Meishu Guo; Guy Smagghe; Renhuai Dai (Arthropod Systematics & Phylogeny)
Iassinae, a widely distributed group of herbivorous pest insects, is a subfamily of Cicadellidae. Previous studies on the phylogeny of Iassinae were mostly based on morphological characteristics, mitochondrial genomes, and molecular fragments (H3, 28S, and 12S), and their phylogenetic relationships were controversial. To better understand Iassinae, we analyzed the phylogenetic relationships among four genera in Iassinae with use of thousands of universal single-copy orthologs and ultraconserved elements extracted from 25 newly sequenced low-coverage whole genome data. Both marker sets provided consistent results across the maximum likelihood and coalescent-based species tree approaches. The phylogenetic results showed that the two genera Batracomorphus and Trocnadella were monophyletic groups, and Krisna a paraphyletic group. For the genus Gessius, we could not explain whether it is monophyletic or paraphyletic since only one species was involved. In this study, the phylogenetic relationship with use of universal single-copy orthologs and ultraconserved elements was stable, and all results supported that Batracomorphus is a sister group of Trocnadella, and that Gessius and Krisna possess a sister relationship. In addition, the divergence time showed that the divergence of Batracomorphus, Trocnadella, Krisna and Gessius began at approximately 49–72 Mya, 33–57 Mya, 51–78 Mya and 17–36 Mya, respectively. These results will help us to understand the phylogeny and evolutionary relationship of Iassinae.